2023
DOI: 10.3390/metabo13080961
|View full text |Cite
|
Sign up to set email alerts
|

The Urine Metabolome of R6/2 and zQ175DN Huntington’s Disease Mouse Models

Roberto Speziale,
Camilla Montesano,
Giulia Di Pietro
et al.

Abstract: Huntington’s disease (HD) is caused by the expansion of a polyglutamine (polyQ)-encoding tract in exon 1 of the huntingtin gene to greater than 35 CAG repeats. It typically has a disease course lasting 15–20 years, and there are currently no disease-modifying therapies available. Thus, there is a need for faithful mouse models of HD to use in preclinical studies of disease mechanisms, target validation, and therapeutic compound testing. A large variety of mouse models of HD were generated, none of which fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The proposed workflow for sample analysis and data quality assurance was based on an efficient metabolomics platform 61 , with some modifications. The detailed workflow description is reported below.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed workflow for sample analysis and data quality assurance was based on an efficient metabolomics platform 61 , with some modifications. The detailed workflow description is reported below.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have observed that restoring insulin signaling via SIRT2 inhibition provides neuronal protection ( Luthi-Carter et al, 2010 ; Arora and Dey, 2016 ). Additionally, liquid chromatography-high-resolution mass spectrometry analysis revealed insulin resistance in the urine of R6/2 mice ( Speziale et al, 2023 ). Transcriptomics investigations have also reported significant changes in several genes involved in glucose uptake and homeostasis ( Sorcs1 , Hh-II , and Vldlr ), with a lower glucose uptake rate in affected tissues and subsequent development of insulin resistance ( Chaves et al, 2017 ) ( Figure 2C ).…”
Section: Insulin Resistance and Neurodegenerative Diseasesmentioning
confidence: 99%